(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Blackberry Publishing House(BPH) is a case study dealing with a sensitive aspect of human behaviour,team building and the effects of Leaders and the leadership process. Working environment in an organisation largely depends on the style of Leadership based directly on the maturity and readiness of the followers. From Telling style when followers are not willing not mature to Delegating, when the followers are willing and very capable,the Leaders have to articulate the style so that the followers remain motivated and are encouraged in achieving their self actualisation. No employee is working for a job alone,but are looking for a career and growth. Leaders usually overlook the aspect of self esteem of an employee and are result oriented for their advancement. BPH has a willing lot of workers, but the malaise of nepotism and strong biases usually dishearten the employees and who in turn loose interest in work. Competence of a boss is well appreciated, but the humane factor in dealing, cannot be overlooked. The higher management has to closely monitor the functioning and set the course right if any deviations are observed,so that a fair deal is given to all. Opportunist leaders should be well avoided, as their reliabilty becomes questionable,and can abandon a ship again at the time of peril. BPH has a competent lot of working professional who have a desire to excel and produce quality work. Lack of opportunity to showcase their efforts because of personal differences show poor professional working, and which cannot be compensated by verbal motivation. Challenging job, rewards and recognition, necessarily not monetarily is a shot- in- the -arm of any employee. Worklife balance has also been playing an important role in the lives of employees and if the same is not maintained, it has a retograde effect on the motivation of employees and results in severe stress,which may culminate in an employee taking an extreme step of quitting the job. Higher Management,quintessentially, plays a pivotal role of ensuring fair play, good working ethics and just that Eustress which makes the employee working and feeling a sense of achievement and satisfaction.